2015
DOI: 10.2147/ijn.s83005
|View full text |Cite
|
Sign up to set email alerts
|

Controlling drug delivery kinetics from mesoporous titania thin films by pore size and surface energy

Abstract: The osseointegration capacity of bone-anchoring implants can be improved by the use of drugs that are administrated by an inbuilt drug delivery system. However, to attain superior control of drug delivery and to have the ability to administer drugs of varying size, including proteins, further material development of drug carriers is needed. Mesoporous materials have shown great potential in drug delivery applications to provide and maintain a drug concentration within the therapeutic window for the desired per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…22 In this study, mesoporous titania thin films were deposited onto titanium implants and subsequently loaded with ALN. In previous in vitro and in vivo studies, it has been demonstrated that such mesoporous titania films are wellsuited as carrier frameworks for different substances, such as ALN, raloxifene, and Mg. 13,23,24 In the present study, the influence of ALN on bone mineralization was evaluated both in vitro and in vivo. The in vitro method used was based on simulated body fluid (SBF), which has been developed by Kokubo et al 25 This method has been proved to mimic the in vivo bone mineralization well.…”
Section: Introductionmentioning
confidence: 99%
“…22 In this study, mesoporous titania thin films were deposited onto titanium implants and subsequently loaded with ALN. In previous in vitro and in vivo studies, it has been demonstrated that such mesoporous titania films are wellsuited as carrier frameworks for different substances, such as ALN, raloxifene, and Mg. 13,23,24 In the present study, the influence of ALN on bone mineralization was evaluated both in vitro and in vivo. The in vitro method used was based on simulated body fluid (SBF), which has been developed by Kokubo et al 25 This method has been proved to mimic the in vivo bone mineralization well.…”
Section: Introductionmentioning
confidence: 99%
“…, Δm=C×Δfn where C is the mass sensitivity constant (17.7 ng⋅Hz −1 ⋅cm −2 ) and n the overtone number (1, 3, 5, and so forth). Prior to analysis, the mesoporous titania matrix was deposited onto Ti QCM‐D sensors (QSX 310, Q‐Sense, Sweden), a methodology proven to result in stable mesoporous thin films . The initial flow in the QCM‐D experiments was pure Milli‐Q H 2 O using a flow rate of 50.0 mL/min until a stable baseline was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to analysis, the mesoporous titania matrix was deposited onto Ti QCM-D sensors (QSX 310, Q-Sense, Sweden), a methodology proven to result in stable mesoporous thin films. 30,36,37,[42][43][44][45] The initial flow in the QCM-D experiments was pure Milli-Q H 2 O using a flow rate of 50.0 mL/ min until a stable baseline was obtained. Thereafter, a flow at 50.0 mL/min of either plerixafor (0.4 mg/mL) or SDF-1a (8.0Á10 24 mg/mL) dissolved in water was added to monitor the drug adsorption into the mesoporous film.…”
Section: Dm52mentioning
confidence: 99%
See 2 more Smart Citations